2018
DOI: 10.1074/jbc.ra118.004512
|View full text |Cite
|
Sign up to set email alerts
|

CARM1 suppresses de novo serine synthesis by promoting PKM2 activity

Abstract: Glucose is a critical nutrient for cell proliferation. However, the molecular pathways that regulate glucose metabolism are still elusive. We discovered that co-activator-associated arginine methyltransferase 1 (CARM1) suppresses glucose metabolism toward serine biosynthesis. By tracing the C-labeled glucose, we found that knockout mouse embryonic fibroblasts exhibit significantly increased serine synthesis than WT cells. This is caused, at least in part, by the reduced pyruvate kinase (PK) activity in these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…In breast cancer cells, coactivator associated arginine methyltransferase 1 (CRAMT) can methylate PKM2 on arginine 445, 447, and 455 to stabilize tetramer formation of PKM2 and shifts the balance of metabolism from OXPHOS to aerobic glycolysis. Inhibition of PKM2 methylation significantly decreases cancer cells’ proliferation, migration, and metastasis 41 . Xu et al.…”
Section: Glucose Metabolism and Cancer Metastasismentioning
confidence: 99%
“…In breast cancer cells, coactivator associated arginine methyltransferase 1 (CRAMT) can methylate PKM2 on arginine 445, 447, and 455 to stabilize tetramer formation of PKM2 and shifts the balance of metabolism from OXPHOS to aerobic glycolysis. Inhibition of PKM2 methylation significantly decreases cancer cells’ proliferation, migration, and metastasis 41 . Xu et al.…”
Section: Glucose Metabolism and Cancer Metastasismentioning
confidence: 99%
“…Recent studies have shown that the low kinase activity of the M2 isoform of pyruvate kinase (PKM2) leads to accumulation of glycolytic intermediates, which can provide substrates for the SSP, and PKM2 activation reduces the SSP flux (Kung et al, 2012;Abeywardana et al, 2018;Ye et al, 2012). To confirm whether SSP inhibition, not PHGDH inhibition itself, affected the proliferation of leukemic cells, we activated PKM2 in both culture conditions.…”
Section: Glut5-low Leukemic Cells Are More Dependent On the Ssp In Fructose-rich Conditionsmentioning
confidence: 99%
“…Under serine starvation, PKM2 is transformed into a monomeric state with low activity and slows the last step of glycolysis, leading to the accumulation of upstream glycolysis intermediates such as 3-PG. The accumulation of raw material 3-PG increases the synthesis of intracellular serine [33][34][35]. In contrast to PKM2, PHGDH can be inhibited by serine [36].…”
Section: Glycine Transamination and De Novo Serine Synthesismentioning
confidence: 99%
“…Serine metabolism can impact the intracellular methylated response through the production of SAM within the process of one-carbon metabolism. SAM is considered the major methyl donor during intracellular methylation reactions, including DNA/RNA and histone methylation [ 35 ]. Although serine is not directly involved in the methylation process, serine starvation reduces global levels of methylation in cancer cells by blocking the methionine cycle [ 59 ].…”
Section: Serine and Senescencementioning
confidence: 99%